Within-domain and across-domain compensation: a systematic review, integrative framework and future research agenda - Rui Wang; Chao Tian (BMC Psychology)
Abstract Different from previous studies on the motives of compensatory consumption, this review focuses on the strategies of compensatory consumption. This literature review aims to introduce two main strategies for compensatory consumption, within-domain and across-domain compensation. Within-domain compensation is a consumption strategy to repair a self-discrepancy in a specific domain, while across-domain compensation refers to a consumption strategy that consumers restore their global self-worth by affirming themselves in other important domains yet unrelated to the self-discrepancies. Based on the SPAR-4-SLR protocol to assemble, arrange and assess literature published from 2008 to 2023 Q1, we chose 65 articles to review. In order to gain a deeper understanding of within-domain and across-domain compensation, we systematically review the existing literature in the field and propose a framework based on the ADO models. Lastly, we discuss the various research directions for within-domain and across-domain compensation from the viewpoint of theory, context, characteristics, and methodology according to the TCCM framework. Researchers, marketers, and advertisers can learn about the latest research related to compensatory consumption strategies in this article.